PHYSICAL ACTIVITY OF STUDENTS AT HIGHER EDUCATIONAL INSTITUTIONS WITH KINESIOLOGY AND HEALTH MAJORS IN THE SETTING OF COVID-19 PANDEMIC - Yaroshyk, Marta; Rymar, Olga; Malanchuk, Halyna; Solovey, Alla; Khanikiants, Olena; Bubela, Oleksiy-Oleg (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The purpose of this study was to discover the peculiarities of students’ physical activities that study at higher educational institutions with kinesiology and health majors in the setting of COVID-19 pandemic. In order to accomplish it, an online survey was conducted among a total of 236 students of Lviv State University of Physical Culture named after Ivan Boberskyj. With its help, we were able to determine both domestic and organized physical activity levels’ self-assessments of the sample group before and during the quarantine restrictions. The majority of the students evaluated their physical activity levels as “excellent” and “good”. No significant changes among the physical activity assessments were not tracked during the quarantine restrictions. We established that 59% of the study group had regularly visited gyms before the pandemic breakout and 12% of the students systematic did home exercises. The remainder of active students (26%) exercised seldom. Before the pandemic, only 3% of the participants had not engaged themselves into organized physical activities. We observed an overall studentship physical activity decrease in terms of instances and intensity during the quarantine limitations. The forms of physical activities were substantially changed. Thus, the students began to stroll more often, as well as train alone or with online-coaches. Cardio and muscle strengthening remained dominant among activities both before and after the quarantine. After the quarantine restriction weakening, half of the study group re-embarked on gym training. 28% of the students continued exercising the same way they did during the quarantine. 12% of the respondents exercised on their owns. 7% of the participants did not return to training. With the respect to the results of this study, we can infer that Ukrainian students prefer group exercises where they can interact with either coach or other participant of the training sessions, as well as modern technologies cannot fully fulfill their needs of physical activity.